2023
DOI: 10.3390/su151310094
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Trends in Low-Energy Development Patterns in China: A Data-Driven Approach

Abstract: China is currently undergoing a transition towards high-quality economic development, and the industrial structure is being optimized. However, there are still regional imbalances in economic development and energy consumption. Therefore, it is necessary to investigate whether the disparities in electricity intensity between provinces and industries can converge over time. This paper investigates the trend towards low-energy consumption in China and verifies the club convergence of electricity intensity across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Another significant aspect that, depending on the development of the situation, can both positively and negatively affect the development of greywater heat recovery systems, is the ecological awareness of society. Wang et al [106] noticed that increased environmental awareness can boost the demand for clean energy production. Wu et al [107] showed that a lack of it can be the main barrier to the development of green building.…”
Section: Opportunities and Threatsmentioning
confidence: 99%
“…Another significant aspect that, depending on the development of the situation, can both positively and negatively affect the development of greywater heat recovery systems, is the ecological awareness of society. Wang et al [106] noticed that increased environmental awareness can boost the demand for clean energy production. Wu et al [107] showed that a lack of it can be the main barrier to the development of green building.…”
Section: Opportunities and Threatsmentioning
confidence: 99%